2015
DOI: 10.3390/catal5042024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Passivation on Photoelectrochemical Water Splitting Performance of WO3 Vertical Plate-Like Films

Abstract: WO3 vertical plate-like arrays provide a direct pathway for charge transport, and thus hold great potential as working electrodes for photoelectrochemical (PEC) water splitting. However, surface recombination due to surface defects hinders the performance improvement. In this work, WO3 vertical plate-like arrays films with HfO2 passivation layer were fabricated via a simple dip-coating method. In the images of transmission electron microscope, a fluffy layer and some small sphere particles existed on the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…However, the fast charge recombination at the surface defect sites (W 5+ and surface states) hinders the overall PEC performance. Several strategies have been proposed to address this issue, such as hydrogen treatment [83,84], co-catalyst deposition [85][86][87] and passivation layer introduction [88,89]. Kim et al reported an efficient surface passivation approach for decreasing the photoelectron trapping event for WO 3 using an Al 2 O 3 overlayer [44].…”
Section: Wo 3 Photoanodesmentioning
confidence: 99%
“…However, the fast charge recombination at the surface defect sites (W 5+ and surface states) hinders the overall PEC performance. Several strategies have been proposed to address this issue, such as hydrogen treatment [83,84], co-catalyst deposition [85][86][87] and passivation layer introduction [88,89]. Kim et al reported an efficient surface passivation approach for decreasing the photoelectron trapping event for WO 3 using an Al 2 O 3 overlayer [44].…”
Section: Wo 3 Photoanodesmentioning
confidence: 99%
“…The existence of several concerns related to the increasing energy demand and the related environmental crisis [1][2][3][4][5][6] indicates the need to identify innovative, effective and low cost solutions. Photoelectrochemical water splitting (PWS) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] is recognised as a promising strategy and it attracts particular interest for storing solar energy into the chemical bonds of hydrogen as fuel [26][27][28], which can be further utilised in fuel cells [29][30][31][32][33][34], internal combustion engines and to progressively decarbonize industrial processes [35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] Herein, tungsten oxide (WO 3 ) has been seen as a promising photoelectrode material for the PEC water oxidation system due to its 2.6-2.8 eV band gap and photostability in water. [12][13][14][15] Furthermore, WO 3 can also provide enough overpotential for the crucial half reaction of oxygen evolution due to its favorable valence position (which is approximately 3 V versus NHE). Recently, Ma and coworkers reported that a mesoporous WO 3 photoanode with a dual oxygen and tungsten vacanciescontaining overlayer could greatly enhance the PEC activity for water oxidation, which was attributed to alleviating charge recombination at the electrode/electrolyte interface.…”
Section: Introductionmentioning
confidence: 99%